(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This paper provides an overview of research related to the use of blended learning in English as a th language/foreign language context. Blended learning is a relatively new field that combines traditional educational approaches with distance and online learning. The use of blended learning is highlighted in recent study investigating the academic and societal benefits of this educational approach.